2012
DOI: 10.1155/2012/593878
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Folate‐Conjugated Pluronic F127/Chitosan Core‐Shell Nanoparticles Encapsulating Doxorubicin for Breast Cancer Treatment

Abstract: A targeting drug delivery system using folate-conjugated pluronic F127/chitosan core-shell nanoparticles was developed to deliver doxorubicin (DOX) to the target cancer cells. First, DOX was encapsulated in pluronic F127 micelle cores in the presence of sodium dodecyl sulfate (SDS) by a self-assembly method. To form a shell, a layer of either chitosan or folate-conjugated chitosan was deposited onto the pluronic micelles. The encapsulation efficiency was approximately58.1±4.7%. The average size of the core-she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 63 publications
(79 reference statements)
4
32
0
Order By: Relevance
“…So, this naturally abundant polysaccharide has taken on an important role in the novel drug delivery systems (DDS) with the purpose of carrying out targeted delivery [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…So, this naturally abundant polysaccharide has taken on an important role in the novel drug delivery systems (DDS) with the purpose of carrying out targeted delivery [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Tahara et al [40] found that A549 cells internalize chitosan-modified poly(DL-lactic-co-glycolic acid) nanospheres much better compared to the unmodified ones. Manaspon et al [12] showed that cellular uptake of chitosan nanoparticles, which have no targeting moiety on the surface, was probably mediated by nonspecific adsorptive endocytosis. The positive charge of chitosan nanoparticles can be easily attracted by negatively charged cell membranes, allowing the particles to be taken into the cells [12].…”
Section: Discussionmentioning
confidence: 99%
“…Manaspon et al [12] showed that cellular uptake of chitosan nanoparticles, which have no targeting moiety on the surface, was probably mediated by nonspecific adsorptive endocytosis. The positive charge of chitosan nanoparticles can be easily attracted by negatively charged cell membranes, allowing the particles to be taken into the cells [12]. However, in the present study it was found that the number of chitosan-stabilized GNPs which penetrate into the cells is not great.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell viability was not disturbed by nanoparticles at concentrations lesser than 1 mg/ml (ref. 43). Folate-conjugated chitosan was loaded with other polymers or inorganic materials like graphene oxide (GO), carbon nanotube (CNT) with the anticancer drug doxorubicin (DOX) through - staking.…”
Section: Doxorubicinmentioning
confidence: 99%